STRATEGIC RISK ANALYSIS OF COMPLEX ENGINEERING SYSTEM UPGRADES - Matthew Cook; John P.T. Mo (European Scientific Journal, ESJ, 2015)
Highly complex bespoke engineering products require upgrades during their long service life. These engineering changes can be risky due to the absence of an engineering baseline and/or multiple undocumented operational changes. They present significant challenges to the engineering contractor in terms of budget overruns, schedule impacts/delays, technical failures and ultimately a disappointed customer. Current risk management methods can be subjective and inaccurate. This paper outlines methodology to potentially predict, identify and visualize risks in a strategic structure which can ultimately lead to establishing necessary risk mitigation actions to significantly reduce and manage the risk of complex engineering system upgrade projects.